Research Methodology: Paradigms, Approaches, Methods and Design - Costa, King; Mpepho, Kwakho; Mfolo, Letlhogonolo; Mokgadi, Martin (My University, 2023)
This abstract covers the main points discussed in the text, as well as the definitions and explanations of research paradigms (positivism, interpretivism, and pragmatism), research approaches (deductive, inductive, and abductive), research methods (quantitative and qualitative), and research design/strategy (experimental design and case study design). It also includes aspects of data collection and data analysis, focusing on the importance of ethical considerations and valid and reliable methodologies. The abstract concludes by highlighting the significance of understanding and aligning these components with research objectives and the nature of the research problem to generate meaningful and reliable findings that contribute to knowledge advancement in various fields of study.
Keywords: Data Collection and Analysis; Research Approach; Research Design; Research Methods; Research Paradigm